2016
DOI: 10.1167/iovs.16-19585
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Pharmacokinetic Analysis of an Intracameral Polycaprolactone Drug Delivery Implant for Glaucoma

Abstract: PurposeWe developed polycaprolactone (PCL) implants that achieve zero-order release of a proprietary ocular hypotensive agent (DE-117) over 6 months.MethodsThe release rates of DE-117–loaded PCL devices were tuned based on an established predictive model and confirmed by in vitro release studies. Devices containing DE-117 and empty devices were implanted intracamerally in normotensive rabbits for up to 8 weeks' duration. Devices were retrieved after rabbits were euthanized and evaluated for tissue adherence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 16 publications
2
54
0
1
Order By: Relevance
“…By providing sustained IOP-lowering effects, drug-delivery systems such as Bimatoprost SR may help to address this unmet need. These new delivery systems may delay the need for more invasive (surgical) treatment by more precisely targeting the drug to sites of action [30,35,36], while providing IOP-lowering effects and tolerability profiles comparable to those of topical therapy [28,37,38]. Other sustained-release products are in various phases of clinical development, including ENV515 (Envisia Therapeutics, Durham, NC, USA), OTX-TIC (Ocular Therapeutix, Bedford, MA, USA), and iDose (Glaukos Corporation, Laguna Hills, CA, USA) for intracameral delivery of travoprost.…”
Section: Discussionmentioning
confidence: 99%
“…By providing sustained IOP-lowering effects, drug-delivery systems such as Bimatoprost SR may help to address this unmet need. These new delivery systems may delay the need for more invasive (surgical) treatment by more precisely targeting the drug to sites of action [30,35,36], while providing IOP-lowering effects and tolerability profiles comparable to those of topical therapy [28,37,38]. Other sustained-release products are in various phases of clinical development, including ENV515 (Envisia Therapeutics, Durham, NC, USA), OTX-TIC (Ocular Therapeutix, Bedford, MA, USA), and iDose (Glaukos Corporation, Laguna Hills, CA, USA) for intracameral delivery of travoprost.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Kim et al were the first to report success with an intracameral DE-117-loaded polycaprolactone (PCL) implant, inserted to the anterior chamber (AC) through a clear corneal incision, for the treatment of glaucoma. [45] In a more recent study in 16 normotensive rabbits, the same group found a statistically significant IOP reduction in eyes implanted with the DE-117 PLC compared with untreated eyes and placebo PCL devices. [46] Tolerability was good and rates of iris trauma and hyphema during the implantation procedure were lower (19%) than in the previous study (29%).…”
Section: De-117mentioning
confidence: 90%
“…In a randomized, investigator‐masked, active‐controlled multicentre phase 3 trial in Japanese patients comparing DE‐117 versus latanoprost 0.005%, the compound wasshown to be similarly effective, although the IOP change from baseline in mean diurnal IOP for DE‐117 and latanoprost was 0.63 mmHg in favour of latanoprost (Lu et al ., ). Attempts are also being made to use it in long‐term intracameral delivery devices (Kim et al ., ). The compound was also shown to be effective in Xalatan non‐responsive patients (Ropo et al ., ).…”
Section: Pg Analogues As Ocular Hypotensive Agentsmentioning
confidence: 97%